Concordance Between Quranic Narrative of Adam and Hindu Narrative of Swayambhuva Manu - Bharat Jhunjhunwala (International Journal of Interreligious and Intercultural Studies, 2023)
Adam was the first Prophet in Islamic tradition while Swayambhuva Manu was the progenitor of the human race in the Hindu tradition. We trace the parallels between the Islamic narrative of Adam and Hindu narrative of Swayambhuva Manu on four narrations. (1) Beginnings in a situation of a primitive stupor; (2) The negative qualities of black mud or darkness were introduced to break the primitive stupor; (3) The beginning of marriage took place at their time; and (4) Adam was a Prophet while Swayambhuva was venerated as the first progenitor of humankind. These parallel narrations suggest that they may have been the same person sometime in the distant past and their details are available to us differently due to the modifications during long time of transmission. Basically, their life narratives concord with each other. This concordance means that the underlying theological concepts in their lives may also be parallel. We find that the theological concepts relating to these two persons in the two religions are non-contradictory also largely concord with each other though certain silences make them appear to be different. This concordance in the narratives and theological concepts can help develop a mutual understanding between the two religions.